An overview of investigation of Fatigue, tensile strength and hardness of the components fabricated through direct metal laser sintering (DMLS) process. (2021) - Kumar Maurya, Nagendra; Sharma, Rohit; Kumar, Nikhil; Kumar, Anubhav; Anand, Piyush; Rai, Prakhar; Singh, Harjeet
Abstract: Direct metal laser sintering (DMLS) is an immerging technology for the fabrication of metallic components directly from the 3D CAD model. In this study, mechanical properties of the components fabricated through DMLS process by various researchers have been reported. From archival literature it is observed that DMLS process has capability to fabricate functional components in small volume. However, the mechanical properties of the components fabricated through this process are inferior as compared to components fabricated through other traditional manufacturing process. Further it has reduced the lead time of product development process. Results depicted that process parameters layer thickness, scan speed, hatch spacing, laser power, and orientation have largest impact on hardness, fatigue and tensile strength of the DMLS printed components.